A case report on necrotizing fasciitis in a hemiplegic patient following an intra-muscular injection - Mendem, Sowjanya; Faraz, M. Aqib Ali; Rao, K. Lankeswar (International Journal Of Community Medicine And Public Health, 2020)
Necrotizing fasciitis (NF) can be defined as a surgical emergency causing the necrosis of the skin, subcutaneous fat, and superficial fascia. It spreads along the fascial planes with or without the presence of cellulitis. It is characterized by the destruction of tissue, systemic toxicity, and may even lead to morbidity and mortality. Higher rates of prevalence were observed in the obese, diabetic, alcoholic, patients with peripheral vascular diseases and immunocompromised populations. There are no definite diagnostic criteria for NF and the laboratory findings may lead to misdiagnosis as cellulitis or abscess. It is usually developed from an injury to the skin, which may occur during trauma, IV drug use, drug administration (via injection), skin infections, ulcer, insect bites, visceral-cutaneous fistulas, surgical complications, percutaneous catheter insertion, abscesses and can even have idiopathic causes. Early diagnosis of the condition, surgical debridement, and optimal antibiotic therapy leads to the improvement in the condition and desired outcomes in the patient. The present study is focused on the successful treatment of necrotizing fasciitis in a hypertensive and hemiplegic patient, following an IM injection of an analgesic, which caused an ulcer and rapidly progressed, leading to necrosis of the affected regions.